Estimating the Effects of Macroeconomic Factors on Investments in Malaysia - Nik Suriati, Nik Hassan (2009)
Investment is one of the components in Gross Domestic Product (GDP). As a GDP component from the current domestic expenditure side, investment has an immediate impact on GDP. GDP will increase if the level in investment in our country is high. This paper presents an analysis of the investment determinant in Malaysia based on neoclassical model with modification for the period from year 1978 to year 2007. In this empirical analysis, a model consists of saving, foreign direct investment, exchange rate, interest rate and inflation is constructed to show domestic investment behavior. Based on Johansen and Juselius approach, in long run, results indicate that saving, foreign direct investment, interest rate and inflation are the determinants of total domestic investment. In case of private investment, it is influenced by saving, foreign direct investment, interest rate, inflation and exchange rate. On the other hand, based on the result of vector error correction model (VECM) that show the short run relationship, saving, foreign direct investment, interest rate, inflation and exchange rate are insignificant in explaining both total domestic investment and private investment. Error Correction component, ECM is the only significant variable for total domestic investment and private investment. ECM is important to show the speed of adjustment. For total domestic investment, it’s significant with 61% adjustment in short run and for private investment; it’s significant with 74% adjustment in short run. This suggests that the suitable policy should be applied based on the significant result to increase domestic investment in Malaysia.